2017
DOI: 10.14740/cr558w
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Myxoma Mimicking Mitral Stenosis

Abstract: Myxoma is the most common primary cardiac tumor and is usually located in the left atrium. Clinical manifestation relies in large part on the size, location, and architecture of the tumor. There are many reports in the literature of cardiac myxomas causing syncope, embolism, even myocardial infarction. We present a rare case of a patient who underwent urgent surgical resection of a large left atrial myxoma mimicking mitral stenosis. The postoperative course of the patient was uncomplicated. One year after surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 5 publications
1
10
1
4
Order By: Relevance
“…These data differ from previous series, which showed TIA as the most frequent neurological presentation of atrial myxoma (9). Nevertheless, multiple studies found percentages of ischemic cerebral infarction similar to the present values (4,5,10). This discrepancy may be associated with different pathological characteristics of atrial myxomas.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…These data differ from previous series, which showed TIA as the most frequent neurological presentation of atrial myxoma (9). Nevertheless, multiple studies found percentages of ischemic cerebral infarction similar to the present values (4,5,10). This discrepancy may be associated with different pathological characteristics of atrial myxomas.…”
Section: Discussioncontrasting
confidence: 93%
“…Manifestation as haemorrhagic stroke is uncommon, and this seems to be related to the formation of cerebral aneurysms (9). The tumor type, size, location and mobility appear to be closely associated with embolism in patients with atrial myxomas (10). Cerebral infarction might recur for non-diagnosed and treated myxomas.…”
Section: Introductionmentioning
confidence: 99%
“…In one patient in the literature with a left atrial myxoma and CNC, a marfanoid phenotype was also notedsimilar to our case. 12 The gold standard for diagnosis is transthoracic echocardiogram, which should be performed as soon as a clinical suspicion is made 11,13,14 Other modalities such as transoesophageal echocardiography (TOE) enable better delineation of the tumor. 13 Cardiac MRI (CMR) and CT may be preferable where a mass has an unusual location or is small in size making it difficult to differentiate from thrombus.…”
Section: Case Reportmentioning
confidence: 99%
“…Клінічні прояви міксом залежать від порушення притоку або відтоку з уражених камер серця, наявності емболіческого синдрому, загальної реакції організму на пухлину. Обструкція кровотоку імітує клінічну картину вади серця, найчастіше стенозів мітрального [34] і трикуспідального клапанів, рідшекомбінованої вади з регургітацією. У дослідженні Г.В.…”
Section: міксоми серцяunclassified